Short Communication: Isolation of Actinomycetes from mangrove ecosystem in Torosiaje, Gorontalo, Indonesia - ABUBAKAR SIDIK KATILI; YULIANA RETNOWATI (Biodiversitas Journal of Biological Diversity, 2017)
Katili AS, Retnowati Y. 2017. Short Communication: Isolation of Actinomycetes from mangrove ecosystem in Torosiaje, Gorontalo, Indonesia. Biodiversitas 18: 826-833. Actinomycetes is a group of positive gram microorganism known to produce secondary metabolic compounds that work as antibiotics, anti-fungus, anti-virus, anti-cancer, and other important enzymes for the industry. This research aimed at discovering the potentials of Actinomycetes of the mangrove ecosystem in Torosiaje, Gorontalo, Indonesia. It focused on finding out the diversity of Actinomycetes at mangrove ecosystem in Torosiaje. Hence, various types of Actinomycetes that have potentials to create secondary metabolic compounds/bioactive compounds for industrial purposes can be found. This purpose can only be attained through isolation of actinomycetes. This isolation was conducted through characterization of morphological characteristics of the colony and the spore, molecular characterization through isolation of DNA genome of the actinomycetes, amplification of 16S rRNA through PCR, sequencing, and reconstruction of the phylogenetic tree. We were able to obtain the actinomycetes isolate from the sediment in rhizosphere area of Ceriops tagal, Bruguiera gymnorrhiza, Xylocarpus sp, Rhizophora apiculata, Avicennia sp, and Sonneratia alba species of mangrove. Each isolated actinomycetes has specific morphological characteristics. The density of isolated actinomycetes in Torosiaje mangrove area was very low with an average of 1 x 105 CFU gram-1 in each sediment.